Dominican Republic : First Review Under the Stand-By Arrangement, Requests for Waivers of Applicability and Modification of Performance Criteria-Staff Report; Staff Supplement; Informational Annex; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
A 28-month Stand-By Arrangement (SBA) for the Dominican Republic was introduced against the global recession. The main objective of the program is to limit the procyclicality of policies. The countercyclical macroeconomic program improved confidence and fostered aggregate demand. Monetary policy remained accommodative with a record low policy rate. Fiscal policy became countercyclical. All structural benchmarks were observed. IMF staff supports the waiver requests and the completion of the first SBA review given the proposed actions and satisfactory performance.